1984
DOI: 10.1159/000183202
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Studies in Hemodialysis Patients before and after Treatment with Low Dialysate Magnesium

Abstract: The magnesium status of 22 hemodialysis patients was studied by analyses of serum, skeletal muscle and peripheral blood lymphocyte levels of magnesium. Despite elevated serum magnesium, normal magnesium levels were noted in skeletal muscle and lymphocytes. 12 patients were exposed to a low dialysate magnesium concentration, resulting in normalization of serum magnesium but no changes in muscle or lymphocyte magnesium, which might indicate slow exchange between these intracellular stores and the extracellular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 10 publications
1
45
1
Order By: Relevance
“…Using a similarly low (0.5 mEq/l) dialysate [Mg], Gonella et al [13] reported predialysis [Mg] of 1.57 ± 0.05 mEq/l (range 1.16-1.82) with 4/12 (33%) of patients having a predialysis [Mg] of <1.5 mEq/l. Using an even lower (0.4 mEq/l) dialysate [Mg] for a duration of 4 months, Nilsson et al [14] reported a mean predialysis [Mg] of 1.86 ± 0.48 mEq/l. The range of values was not given, but based on the reported variance in their data, probably no more than 20% had plasma [Mg] <1.5 mEq/l.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a similarly low (0.5 mEq/l) dialysate [Mg], Gonella et al [13] reported predialysis [Mg] of 1.57 ± 0.05 mEq/l (range 1.16-1.82) with 4/12 (33%) of patients having a predialysis [Mg] of <1.5 mEq/l. Using an even lower (0.4 mEq/l) dialysate [Mg] for a duration of 4 months, Nilsson et al [14] reported a mean predialysis [Mg] of 1.86 ± 0.48 mEq/l. The range of values was not given, but based on the reported variance in their data, probably no more than 20% had plasma [Mg] <1.5 mEq/l.…”
Section: Discussionmentioning
confidence: 99%
“…Lower dialysate [Mg] (i.e. 0.4-0.5 mEq/l) has generally not resulted in hypomagnesemia in previous studies [1,13,14,16,18]. …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Serum Mg levels showed an independent inverse relationship with intact PTH levels in pre-dialysis ESRD patients [55] and dialysis patients [56,57]. Interventional studies showed that dialysate Mg concentration and Mg-containing phosphate binders affected intact PTH levels [58,59]. Mg suppresses PTH secretion via the activation of Ca sensing receptor, although Mg is 2-to 3-fold less potent than Ca.…”
Section: Mg and Dialysis Therapymentioning
confidence: 99%
“…Other factors, such as xerosis, increases in skin mast cells, hyperparathyroidism, high serum magnesium, and increased vitamin A, may lead to onset or may aggravate uremic pruritus (7)(8)(9)(10)(11). Not only is the treatment of uremic pruritus complex (12), but dialysis also has a mild effect on it (13), as the severity of pruritus can increase on the day of dialysis therapy or on the following day (14).…”
Section: Introductionmentioning
confidence: 99%